The Ritual Economy of Death: An Analysis of the Tulak Breuh Tradition and Fidyat al-Salāh in Acehnese Society, Indonesia - Muhammad Zukhdi (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
This article examines the practice of fidyat ‘ransom’ for prayer (al-ṣalāh) for the deceased in North Aceh through the lens of vernacularizing fiqh, explaining how textual norms are translated into socially legitimate local practices. Employing a qualitative design—library research on Shāfiʿī fiqh and cross-madhhab comparison, combined with fieldwork (observation, in-depth interviews, documentation) across several sub-districts—the study maps operational definitions, normative bases, and modes of implementation, including the tulak breuh tradition (a rotation of rice-based almsgiving). Findings show that what is locally called “fidyat al-ṣalāh” operates primarily as almsgiving/ihdāʾ al-thawāb and, in specific cases, via the Ḥanafī route contingent on waṣiyya (valued at ṣadaqat al-fiṭr and drawn from one-third of the estate); practices are non-coercive and prioritize eligible recipients. Clerical reasoning clusters into three types: first, tradition-solidarity (communal almsgiving), second, iḥtiyāṭ within Shāfiʿī (qawl ḍaʿīf; one mudd= 650–700 grams of rice; per missed prayer) as a personal charity, and third the Ḥanafī position requiring a valid will. Tulak breuh functions as a socio-economic infrastructure that renders the practice feasible (cost-sharing) and legitimate (local authority, ʿurf). The article contributes by refining the operational-normative framework of fidyah/kaffārah for prayer, proposing a model of fiqh vernacularization for bodily acts of worship, and offering practical implications: terminological education, enforcement of waṣiyya and one-third limits, recipient prioritization, operational measures, and basic record-keeping.